Local vs global processing in Williams syndrome. (May 2021) - Mattavelli, Giulia; Costanzo, Floriana; Menghini, Deny; Vicari, Stefano; Papagno, Costanza
Abstract: Background: It has long been debated whether in Williams syndrome (WS) there is a preferential processing of local with respect to global forms, in contrast to the typical 'global advantage' in healthy individuals, which in WS seems to exist only for faces. Aims: We aimed at verifying it and to assess the role of stimulus familiarity by comparing performances with faces to those with other objects using the same type of task. Methods and procedure: A group of children and adolescents with WS and controls with typical development performed a modified version of three tasks: Mooney (with faces and/or guitars), Jane (with faces and houses) and Navon task. Outcomes and results: Individuals with WS were able to process at a global level not only faces but also objects, although they were impaired when they had to compare or discriminate between two stimuli. All groups showed an advantage for global processing, with familiarity improving it. However, WS participants did not benefit from familiarity as much as typically developing young individuals. Conclusions and implications: Peculiar abilities for face stimuli in WS did not emerge nor did a clear facilitation related to object familiarity. These results are useful for planning effective interventions.